Digitalization Disclosure and Accounting Information Quality - Aditya Harry Pratama; Sany Dwita; Rabihah Md Sum (Universitas Negeri Padang in collaboration with The Institute of Indonesia Chartered Accountant (IAI), 2024)
Non-Indexed Publication